2021
DOI: 10.3390/jof7020143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Yellow Laccase from Botrytis cinerea 241

Abstract: Typical laccases have four copper atoms, which form three different copper centers, of which the T1 copper is responsible for the blue color of the enzyme and gives it a characteristic absorbance around 610 nm. Several laccases have unusual spectral properties and are referred to as yellow or white laccases. Only two yellow laccases from the Ascomycota phylum have been described previously, and only one amino acid sequence of those enzymes is available. A yellow laccase Bcl1 from Botrytis cinerea strain 241 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…GluLac and TmtLac optimal temperature was similar to reported ones (do Rosário Freixo et al, 2012;Radveikien ė et al, 2021). Some laccases showed higher optimal temperatures up to 80 • C from strains of T. versicolor (Freixo et al, 2008b) and T. oriantalis (Zheng et al, 2017).…”
Section: Crude Glulacsupporting
confidence: 86%
See 1 more Smart Citation
“…GluLac and TmtLac optimal temperature was similar to reported ones (do Rosário Freixo et al, 2012;Radveikien ė et al, 2021). Some laccases showed higher optimal temperatures up to 80 • C from strains of T. versicolor (Freixo et al, 2008b) and T. oriantalis (Zheng et al, 2017).…”
Section: Crude Glulacsupporting
confidence: 86%
“…AA. Leontievsky et al, 1997) but many other theories have been proposed afterwards, to understand the mechanism monitoring the shifting of the blue laccase to yellow one, including changes in oxidation level (Radveikien ė et al, 2021), structural sphere (Mate et al, 2013), glycosylation state (Mot ¸ et al, 2012), and interaction with metal ions (Radveikien ė et al, 2021). The evidence to be sought from an industrial standpoint will be whether the difference in color of the yellow laccase produced on lignocellulosic waste has an impact on its catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a typical laccase molecule contains four copper atoms with three types of copper sites (T1, T2, and T3), both type I and type III copper ions have the characteristic absorption in the UV–vis spectrum except for type II (Dwivedi et al 2011 ; Rivera-Hoyos et al 2013 ). Herein, the absorption peak at 610 nm represents the T1 copper site of typical blue laccase, while the shoulder around 330 nm represents the T3 copper site of laccase (Radveikienė et al 2021 ). The UV–vis spectrum of CGLac performed a characteristic absorption peak of protein near 280 nm, but no peak near 610 nm and 330 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the types of laccases probably relate to strains and growth conditions. Radveikienė et al ( 2021 ) reported Botrytis cinerea 241 secreted two different laccases (blue and yellow laccases) depending on the cultivation conditions. They found the medium with lower copper concentration was more efficient for yellow laccase production.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of the T1 site at 605 nm (in the Lac from Trametes versicolor ) is the cause of the blue color of Lac [ 8 ]. However, some laccases with an altered catalytic site structure may appear “yellow“ or “white“ [ 8 , 9 , 10 ]. We refer to previous studies [ 1 , 7 , 8 , 11 , 12 ] for an explanation of the catalytic mechanism and the structure-activity relationships in Lacs.…”
Section: Introductionmentioning
confidence: 99%